PERAN PENERAPAN ANALISIS RANTAI NILAI TERHADAP EFISIENSI BIAYA GUNA MENCAPAI KEUNGGULAN KOMPETITIF - Rayyes, Fishal; Retnani, Endang Dwi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
The purpose of this research is to explain the use of value chain analysis and cost driver onactivities whichform value. It has been expected from the explanation of the use of the value chainanalysis can provide description to the management to conduct cost efficiency to achievecompetitive advantage. This research applies qualitative approach. A qualitative approach isdirected to find out how the implementation of value chain analysis to achieve the competitiveadvantage. The result of the research shows that Activities which are not value-added warehousingactivity. At the infrastructure activityof the company and the activity of the cafe can be optimized,such as vehicle activity which raises the cost of the vehicle. It can be concluded that by analyzingthe activity of the company value chain can eliminate the activity and conduct cost reduction, sothat the company is working effectively to achieve competitive advantage.Keywords: value chain, cost efficiency, competitive advantage.